Sistem Pengupahan Penyadap Karet Ditinjau Dalam Fiqh Muamalah - Ahmatnijar, Lili Rahmawati Siregar & Muhammad Arsad Nasution & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The wage system for rubber tappers in the village of siparau, sub-districkof Barumun Tengah, padang lawas regency was motivated by the fact that the wages of rubber tappers were increased unilaterally and were not in accordance with the agreement or contract made when the agreement was made, there was no trasparency and detailed explanation regarding the regarding the reduction in wages made by the owner. Rubber plantation based on the above background, the purpose of this research is ti find out how the wage system increases and decreases by rubber plantation owners in Siparau village, Barumun Tengah District, Padang Lawas Regency and to find out how figh Muamalah’s review of wages increases and decreases by rubber plantation owners. In the village of Barumun Tengah District, Padang Lawas Regency.This research. Sources of data in this study are data, primary and skunde data. Data collection techniques used field studies, namely interviews, documentation and literature study. Interviews were conducted with rubber plantation onwners. Rubber tappers, village beads and religious leaders in siparau village, Barumun TengahDistrict, Padang Lawas Regency data processing and data analysis techniques for this research are that after complete data has been collected, the next step is to carry out data analysis processing and the results of this study indicate that the rubber tappers wage system in the village Siparau, Barumun Tengah Disrtict, Padang Lawas Regency is by means of verbal, the practice of wage rubber tapping that occurs in Siparau Village, Barumun Tengah District, Padang Lawas Regency is not fully in accordance with muamalah fiqh studies because in terms of harmony and piarat requirements, ujrah must be clear and know to both parties. Likewise with the provisions of the principles of trust ( honesty). Justice, and definite agreements that have not been fulfilled in ist implementation.